2017
DOI: 10.3389/fpsyg.2017.01528
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Ostracism Seen through the Lens of Power

Abstract: Drawing on approach/inhibition theory of power, we investigated two factors that influence the manner by which victims react to workplace ostracism: the hierarchical status of the ostracizer and the level of an ostracizee's external social support including family, friends, and significant others. Across an experimental vignette study (Study 1) and a field study (Study 2), we found support for a three-way interaction with felt ostracism, ostracizee external social support, and ostracizer status influencing vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 121 publications
(155 reference statements)
3
46
0
2
Order By: Relevance
“…In certain instances, it may happen unintentionally when the source is too busy or not aware that his or her behavior socially ignores someone else (Al-J o u r n a l P r e -p r o o f Atwi, 2017;Chung and Kim, 2017). Whether it is intentional or unintentional, ostracized employees tend to feel humiliated, powerless, angry, stressed, dissatisfied, and revengeful, resulting in negative behavior (Fiset et al, 2017;Gkorezis et al, 2016;Liu and Xia, 2016;. According to Gkorezis et al, (2016), WO is likely to undermine several fundamental human needs of the victims, particularly the need for belongingness, selfesteem, a meaningful existence, and control.…”
Section: Workplace Ostracismmentioning
confidence: 99%
“…In certain instances, it may happen unintentionally when the source is too busy or not aware that his or her behavior socially ignores someone else (Al-J o u r n a l P r e -p r o o f Atwi, 2017;Chung and Kim, 2017). Whether it is intentional or unintentional, ostracized employees tend to feel humiliated, powerless, angry, stressed, dissatisfied, and revengeful, resulting in negative behavior (Fiset et al, 2017;Gkorezis et al, 2016;Liu and Xia, 2016;. According to Gkorezis et al, (2016), WO is likely to undermine several fundamental human needs of the victims, particularly the need for belongingness, selfesteem, a meaningful existence, and control.…”
Section: Workplace Ostracismmentioning
confidence: 99%
“…First, regarding the supervisor factors, we found that narcissistic tendencies, power awareness, stereotypes, and results orientation may trigger ostracism inclination of a supervisor. Although research has explored the traits and roles of ostracizers, such as power and status authority (Fiset et al, 2017 ), studies are relatively scant and there is not yet a unified research framework. Through case studies, this paper systematically explores the leadership factors that determine the extent to which supervisors practice leadership ostracism.…”
Section: Discussionmentioning
confidence: 99%
“…Sanderson further claims that power relations between these sides play an active role. Concepts of the ostracised individual as 'target' or 'victim' are also used by other sources (Fiset et al, 2017). Liu and Xia (2016) argue that because ostracism is based on subjective perception, the situation perceived as ostracising by one individual may not be so perceived by another.…”
Section: Workplace Ostracismmentioning
confidence: 99%
“…Ostracism is an important stress factor (Williams, 2007) and also affects many variables in organisational environments. Prior research shows that workplace ostracism negatively affects organisational-citizenship behaviour (Fiset et al, 2017), personorganisation fit (Chung, 2015), organisational commitment (Hitlan et al, 2006b), work engagement, satisfaction with one's supervisor and co-workers (Hitlan et al, 2006a) and helping behaviours (Balliet & Ferris, 2013;Mok & De Cremer, 2016). On the other hand, workplace ostracism is positively associated with work-family conflict (Liu et al, 2013), perceived racism and discrimination (Wirth & Williams, 2009), social anxiety (Zadro et al, 2006), organisational silence (Gkorezis et al, 2016), intention to quit (Renn et al, 2013) and non-pro-social behaviours (Balliet & Ferris, 2013;Jones et al, 2009).…”
Section: Workplace Ostracismmentioning
confidence: 99%
See 1 more Smart Citation